Scratch-resistant antibacterial TPU composite material and preparation method thereof
By combining modified aspentin nanosuspension and copper acetate, an antibacterial chain extender is prepared and chain extending polymerized with polyurethane prepolymers, which solves the problem of insufficient antibacterial performance and easy destruction of TPU materials in high usage frequency and special environments, and realizes the long-lasting and effective antibacterial, excellent mechanical properties and self-healing ability of TPU materials.
Patent Information
- Application Number
- CN202411788692.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional TPU materials have problems such as insufficient antibacterial performance, easy mechanical properties to damage, and insulating properties that are not conducive to electrical detection signal conduction in high usage frequency and special environments.
By combining modified aspentin nanosuspension and copper acetate, an antibacterial chain extender is prepared and extended polymerized with polyurethane prepolymer to form a dynamic crosslinking network to improve the antibacterial, mechanical and self-healing properties of TPU materials.
The long-lasting and effective antibacterial ability, excellent mechanical properties and self-repair ability of TPU materials are achieved, avoiding the negative impact of antibacterial agents on material wear resistance and extending service life.
Smart Images

Figure CN119570234A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, in particular to a scratch-resistant antibacterial TPU composite material and a preparation method thereof. Background Art
[0002] TPU is a type of polymer material between rubber and plastic. Due to its excellent mechanical properties, elasticity, wear resistance and chemical stability, it is widely used in electronic equipment casings, medical devices, footwear, automotive parts and other fields. However, with the diversification of application scenarios, especially in high-frequency use and special environments, such as smart wearable devices, traditional TPU materials have insufficient antibacterial properties, frequent stretching and deformation during use leads to the destruction of mechanical properties, and the insulation of TPU materials is not conducive to the transmission of electrical detection signals.
[0003] In order to improve the antibacterial properties of TPU materials, the existing method is often to add antibacterial agents to TPU materials. These antibacterial agents are directly mixed with TPU materials at high speed for extrusion. Not only are they easily dispersed unevenly in the material, resulting in insufficient local antibacterial effect or excessive precipitation, affecting the environmental friendliness of the material, but simple mixing can easily cause the antibacterial agent to fall off the TPU matrix over time, resulting in poor antibacterial durability of the material. At the same time, the antibacterial agent is often not highly compatible with TPU materials, which can easily cause a decrease in the mechanical properties of the material and interface defects, seriously affecting the wear resistance and service life of the TPU material. Summary of the invention
[0004] In order to solve the above technical defects, the present invention has developed a scratch-resistant antibacterial TPU composite material and its preparation process which can maintain the wear resistance of the material itself while having long-lasting and effective antibacterial ability, excellent mechanical properties and self-repairing ability.
[0005] A method for preparing a scratch-resistant antibacterial TPU composite material comprises the following steps:
[0006] S1: Preparation of modified chrysin nanosuspension
[0007] The chrysin solution is prepared by dissolving chrysin in anhydrous pyridine, succinic anhydride is dissolved in anhydrous pyridine by heating and stirring to obtain a succinic anhydride solution, the chrysin solution is added dropwise to the succinic anhydride solution under stirring, and then heated, kept at low temperature overnight, and rotary evaporated, and then dissolved by tetrahydrofuran to obtain a mixed organic solvent, and a stabilizer solution is prepared by uniformly mixing poloxamer 188, carbomer and deionized water, and the mixed organic solvent is quickly injected into the stabilizer solution and ultrasonically treated, and magnetically stirred to obtain a modified chrysin nanosuspension;
[0008] S2: Preparation of antimicrobial chain extenders
[0009] The modified chrysin nanosuspension and copper acetate are mixed and the pH is adjusted, and the copper ion coordinated modified chrysin is obtained after stirring and drying, and the copper ion coordinated modified chrysin and 1,4-butanediol are placed in anhydrous tetrahydrofuran and stirred to obtain an antibacterial chain extender;
[0010] S3: Chain extension polymerization of polyurethane prepolymer
[0011] The polycaprolactone diol is dehydrated and dried, and then mixed with isophorone diisocyanate to obtain a polyurethane prepolymer, and then an antibacterial chain extender is quickly added to the polyurethane prepolymer while maintaining a high temperature, and the reaction is fully stirred and dried to obtain an antibacterial high-elastic TPU;
[0012] S4: Composite of antibacterial and highly elastic TPU materials
[0013] Graphene oxide was prepared by an improved Hummers method. Graphene oxide, ethanol and silane coupling agent KH570 were mixed and reacted to obtain a graphene oxide solution. The graphene oxide solution was then vacuum filtered to form a membrane to obtain a graphene oxide film, which was then reduced by hydrogen iodide vapor to obtain a graphene conductive paper. Antibacterial high-elastic TPU, zircon powder, epoxy soybean oil, stearic acid and diisopropylbenzene peroxide were mixed at a high speed and then extruded and calendered to obtain a TPU composite film. Epoxy resin adhesive was applied to the surface of the graphene conductive paper and then the TPU composite film-graphene conductive paper-TPU composite film sandwich structure was stacked and pressed to obtain a scratch-resistant antibacterial TPU composite material.
[0014] Furthermore, step S1 of preparing the modified chrysin nanosuspension comprises the following steps:
[0015] S1.1: 4-6 parts by weight of chrysin is placed in a container, and then 20-25 parts by weight of anhydrous pyridine is added and stirred until the chrysin is completely dissolved to obtain a chrysin solution. Then 1-2 parts by weight of succinic anhydride and 40-50 parts by weight of anhydrous pyridine are mixed and placed in a container, stirred at a stirring speed of 600-800 rpm for 1-2 minutes, and then placed in an oven, and the oven temperature is adjusted to 60-65°C and heated for 25-30 minutes. After taking out, the mixture is stirred again at a stirring speed of 600-800 rpm. The mixture was stirred at 400 ° C for 2-3 minutes, and then continued to be placed in an oven and heated at a temperature of 65-70 ° C for 20-25 minutes to obtain a succinic anhydride solution, and the chrysin solution was added dropwise to the succinic anhydride solution under stirring. After the addition was completed, it was placed in an oven at 60-65 ° C and heated for 6-8 hours. After cooling to room temperature, it was allowed to stand at 2-3 ° C overnight, and then rotary evaporated at a temperature of 65-70 ° C for 25-30 minutes, and then 60-80 parts by weight of tetrahydrofuran was added to dissolve it to obtain a mixed organic solvent;
[0016] S1.2: Poloxamer 188, carbomer and deionized water are mixed and stirred at a mass ratio of 1: (1-1.5): (150-180) to obtain a stabilizer solution, 20-25 parts by weight of the stabilizer solution are placed in a container, and then 1-2 parts by weight of a mixed organic solvent are quickly injected into the stabilizer solution using a syringe, and then placed in an ultrasonic cleaning machine for 8-10 minutes at an ultrasonic power of 400-450 W, and magnetically stirred at 65-70° C. for 2-3 hours to obtain a modified chrysin nanosuspension.
[0017] Furthermore, the preparation of the antimicrobial chain extender in step S2 comprises the following steps:
[0018] S2.1: 20-25 parts by weight of the modified chrysin nanosuspension and 4-5 parts by weight of copper acetate are mixed in a container, a pH adjuster is added to adjust the pH to 7.5-8, and then stirred at a stirring speed of 200-250 rpm for 2-3 hours, and then placed in a vacuum drying oven at a temperature of 40-50° C. to obtain copper ion coordinated modified chrysin;
[0019] S2.2: The copper ion coordinated modified chrysin obtained in step S2.1 and 8-10 parts by weight of 1,4-butanediol are placed in a container, 18-20 parts by weight of anhydrous tetrahydrofuran are added and stirred for 1.5-2 hours to fully mix the copper ion coordinated modified chrysin and 1,4-butanediol to obtain an antibacterial chain extender.
[0020] Furthermore, the chain extension polymerization of the polyurethane prepolymer in step S3 comprises the following steps:
[0021] S3.1: 20-25 parts by weight of polycaprolactone diol is placed in a vacuum oven at 115-120°C for dehydration for 2-3 hours, and the temperature is cooled to 75-80°C while maintaining the vacuum environment. Then, the mixture is taken out and placed in a container equipped with a stirring device, and 8-10 parts by weight of isophorone diisocyanate is added. The mixture is heated in an oil bath and maintained at 80-85°C. After stirring for 25-30 minutes, stirring is continued, and 0.03-0.05wt% of dibutyltin dilaurate is added dropwise using a syringe, and then nitrogen is introduced for protection. After heat preservation for 3-4 hours, a polyurethane prepolymer is obtained;
[0022] S3.2: Keep the temperature of the polyurethane prepolymer obtained in step S3.1 at 80-85°C, then quickly add the antibacterial chain extender obtained in step S2.2, mix thoroughly at a stirring speed of 400-450rpm, then keep warm for reaction for 3-3.5 hours, place in a vacuum oven at 100-105°C for 3-4 hours, then place in a forced air drying oven, and force dry at 60-65°C for 10-12 hours to obtain an antibacterial high-elastic TPU.
[0023] Furthermore, step S4 of compounding the antibacterial high-elastic TPU material comprises the following steps:
[0024] S4.1: Graphene oxide is prepared by an improved Hummers method, 15-20 parts by weight of graphene oxide is taken, added to a container containing 120-150 parts by weight of ethanol, and then 0.2-0.3 parts by weight of silane coupling agent KH570 is added while stirring, and the mixture is reacted at 45-65°C for 2-3 hours to obtain a graphene oxide solution, the graphene oxide solution is formed into a film by vacuum filtration and placed in an oven at 55-60°C for drying to obtain a graphene oxide film, the graphene oxide film is suspended in a high-pressure reactor by a thin wire, and then 15-20 parts by weight of hydrogen iodide solution is added below, and the graphene oxide film is heated to 100-105°C for 2-3 hours of steam reduction, and then rinsed with ethanol and distilled water in turn, and then placed in a vacuum drying oven at 60-65°C for drying to obtain graphene conductive paper;
[0025] S4.2: Take 60-80 parts by weight of antibacterial high-elastic TPU, 2-3 parts by weight of zircon powder, 0.6-0.8 parts by weight of epoxy soybean oil, 0.8-1 parts by weight of stearic acid and 0.8-1 parts by weight of diisopropylbenzene peroxide, put them in a high-speed mixer for high-speed mixing to obtain a premix, add the premix into a twin-screw extruder for extrusion and then calendering to obtain a TPU composite film, coat the upper and lower surfaces of the graphene conductive paper obtained in step S4.1 with epoxy resin adhesive, and then overlap and press in a sandwich structure of TPU composite film-graphene conductive paper-TPU composite film to obtain a scratch-resistant antibacterial TPU composite material.
[0026] Furthermore, the pH adjuster in step S2.1 is triethylamine.
[0027] Furthermore, in step S4.2, the premix is extruded through a twin-screw extruder and calendered into a TPU film with a thickness of 1-2 mm.
[0028] A scratch-resistant antibacterial TPU composite material is prepared by the preparation method of the scratch-resistant antibacterial TPU composite material.
[0029] The beneficial effects are as follows: 1. After the modified chrysin nanosuspension and copper acetate are mixed, the pH of the system is adjusted to coordinate the copper ions and the modified chrysin, and then the antibacterial chain extender is prepared with 1,4-butanediol. In the subsequent chain extension polymerization reaction with the polyurethane prepolymer, the hydroxyl group in the modified chrysin can produce a chain extension reaction on the isophorone diisocyanate in the polyurethane prepolymer, and the carboxyl group coordinated with the copper ions in the modified chrysin can provide a metal coordination center. The two cooperate to jointly construct a dynamic cross-linked network of the polyurethane, and more hydrogen bonds are introduced into the polyurethane polymer chain, so that the prepared TPU material has better hydrogen bond self-repairing ability and mechanical properties. In addition, the copper ions can also provide excellent antibacterial ability for the TPU material, and can effectively avoid the influence of the antibacterial agent and the hard filler on the wear resistance of the TPU material. The TPU composite material prepared by using the antibacterial high-elastic TPU can provide harmful bacteria for killing during the wearing process, and can effectively avoid the problem of the service life of the TPU composite material being reduced due to frequent scratching and stretching.
[0030] 2. The present invention modifies 4-6 parts by weight of chrysin by using 1-2 parts by weight of succinic anhydride, and by controlling the dosage, a hydroxyl group in chrysin is converted into an ester bond and a carboxylic acid group, thereby enhancing the electron supply capacity of chrysin and providing two oxygen atoms to participate in metal ion coordination at the same time, thereby increasing the number of coordination sites and improving the subsequent coordination capacity with copper ions. In the process of chain extension polymerization of polyurethane prepolymer, a denser metal coordination center can be provided, thereby constructing a more compact and stable cross-linked network, and improving the mechanical properties of antibacterial and highly elastic TPU.
[0031] 3. The present invention prepares a stabilizer solution by mixing poloxamer 188, carbomer and deionized water, and then quickly injects the mixed organic solvent into the stabilizer solution, and then performs ultrasonic treatment and magnetic stirring to prepare a modified chrysin nanosuspension, so that the modified chrysin is uniformly dispersed in the aqueous solution with a smaller particle size, which can greatly increase the subsequent contact area with copper acetate, thereby improving the coordination effect of copper ions and modified chrysin, which is helpful to form a tighter cross-linked network in the subsequent preparation process of antibacterial high-elastic TPU, thereby improving the mechanical properties of the TPU material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a flow chart of the preparation method of the scratch-resistant antibacterial TPU composite material used in the embodiments of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] A scratch-resistant antibacterial TPU composite material and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0036] S1: Preparation of modified chrysin nanosuspension
[0037] S1.1: 4 parts by weight of chrysin are placed in a container, and then 20 parts by weight of anhydrous pyridine are added and stirred until the chrysin is completely dissolved to obtain a chrysin solution, and then 1 part by weight of succinic anhydride and 40 parts by weight of anhydrous pyridine are mixed and placed in a container, stirred at a stirring speed of 600 rpm for 1 minute, and then placed in an oven, the oven temperature is adjusted to 60°C and heated for 25 minutes, and then taken out and stirred again at a stirring speed of 600 rpm for 2 minutes, and then continued to be placed in an oven and heated at a temperature of 65°C for 20 minutes to obtain a succinic anhydride solution, and the chrysin solution is added dropwise to the succinic anhydride solution under stirring. After the addition is completed, it is placed in an oven at 60°C and heated for 6 hours, cooled to room temperature, and then allowed to stand overnight at 2°C, and then rotary evaporated at a temperature of 65°C for 25 minutes, and then 60 parts by weight of tetrahydrofuran are added to dissolve to obtain a mixed organic solvent;
[0038] S1.2: Poloxamer 188, carbomer and deionized water are mixed and stirred at a mass ratio of 1:1:150 to obtain a stabilizer solution, 20 parts by weight of the stabilizer solution are placed in a container, and then 1 part by weight of the mixed organic solvent is quickly injected into the stabilizer solution using a syringe, and then placed in an ultrasonic cleaner for 8 minutes at an ultrasonic power of 400 W, and magnetically stirred at 65°C for 2 hours to obtain a modified chrysin nanosuspension.
[0039] S2: Preparation of antimicrobial chain extenders
[0040] S2.1: 20 parts by weight of the modified chrysin nanosuspension and 4 parts by weight of copper acetate are mixed in a container, triethylamine is added to adjust the pH to 7.5, and the mixture is stirred at a stirring speed of 200 rpm for 2 hours, and then dried in a vacuum drying oven at a temperature of 40° C. to obtain copper ion coordinated modified chrysin;
[0041] S2.2: The copper ion coordinated modified chrysin obtained in step S2.1 and 8 parts by weight of 1,4-butanediol are placed in a container, 18 parts by weight of anhydrous tetrahydrofuran are added and stirring is continued for 1.5 hours to fully mix the copper ion coordinated modified chrysin and 1,4-butanediol to obtain an antibacterial chain extender.
[0042] S3: Chain extension polymerization of polyurethane prepolymer
[0043] S3.1: 20 parts by weight of polycaprolactone diol were placed in a vacuum oven at 115°C for dehydration for 2 hours, and the mixture was taken out after being cooled to 75°C while maintaining the vacuum environment, and then placed in a container equipped with a stirring device, 8 parts by weight of isophorone diisocyanate were added, and the mixture was heated in an oil bath and maintained at 80°C. After stirring for 25 minutes, 0.03 wt% of dibutyltin dilaurate was added dropwise using a syringe, and then nitrogen was introduced for protection. After keeping the temperature for 3 hours, a polyurethane prepolymer was obtained;
[0044] S3.2: Keep the temperature of the polyurethane prepolymer obtained in step S3.1 at 80°C, then quickly add the antibacterial chain extender obtained in step S2.2, mix thoroughly at a stirring speed of 400 rpm, then keep the reaction warm for 3 hours, place it in a vacuum oven at 100°C for 3 hours, then place it in a forced air drying oven and force dry it at 60°C for 10 hours to obtain an antibacterial high-elastic TPU.
[0045] S4: Composite of antibacterial and highly elastic TPU materials
[0046] S4.1: Graphene oxide is prepared by using an improved Hummers method, 15 parts by weight of graphene oxide is taken and added to a container containing 120 parts by weight of ethanol, and then 0.2 parts by weight of silane coupling agent KH570 is added while stirring, and the mixture is reacted at 45°C for 2 hours to obtain a graphene oxide solution, the graphene oxide solution is formed into a film by vacuum filtration and placed in an oven at 55°C for drying to obtain a graphene oxide film, the graphene oxide film is suspended in a high-pressure reactor by a thin wire, and then 15 parts by weight of hydrogen iodide solution is added below, and the graphene oxide film is heated to 100°C for 2 hours of steam reduction, and then rinsed with ethanol and distilled water in turn, and then placed in a vacuum drying oven at 60°C for drying to obtain graphene conductive paper;
[0047] S4.2: Take 60 parts by weight of antibacterial high-elastic TPU, 2 parts by weight of zircon powder, 0.6 parts by weight of epoxy soybean oil, 0.8 parts by weight of stearic acid and 0.8 parts by weight of diisopropylbenzene peroxide, put them in a high-speed mixer for high-speed mixing to obtain a premix, add the premix into a twin-screw extruder, extrude it and then calender it to obtain a TPU composite film with a thickness of 1 mm, coat the upper and lower surfaces of the graphene conductive paper obtained in step S4.1 with epoxy resin adhesive, and then overlap and press it in a sandwich structure of TPU composite film-graphene conductive paper-TPU composite film to obtain a scratch-resistant antibacterial TPU composite material.
[0048] Example 2
[0049] A scratch-resistant antibacterial TPU composite material and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0050] S1: Preparation of modified chrysin nanosuspension
[0051] S1.1: 6 parts by weight of chrysin are placed in a container, and then 25 parts by weight of anhydrous pyridine are added and stirred until the chrysin is completely dissolved to obtain a chrysin solution, and then 2 parts by weight of succinic anhydride and 50 parts by weight of anhydrous pyridine are mixed and placed in a container, stirred at a stirring speed of 600 rpm for 1 minute, and then placed in an oven, and the oven temperature is adjusted to 60°C and heated for 25 minutes. After taking out, the mixture is stirred again at a stirring speed of 600 rpm for 2 minutes, and then continued to be placed in an oven and heated at a temperature of 65°C for 20 minutes to obtain a succinic anhydride solution, and the chrysin solution is added dropwise to the succinic anhydride solution under stirring. After the addition is completed, the mixture is placed in an oven at 60°C and heated for 6 hours, cooled to room temperature, and then allowed to stand overnight at 2°C, and then rotary evaporated at a temperature of 65°C for 25 minutes, and then 80 parts by weight of tetrahydrofuran are added to dissolve the mixture to obtain a mixed organic solvent;
[0052] S1.2: Poloxamer 188, carbomer and deionized water are mixed and stirred in a mass ratio of 1:1.5:180 to obtain a stabilizer solution, 25 parts by weight of the stabilizer solution are placed in a container, and then 2 parts by weight of the mixed organic solvent are quickly injected into the stabilizer solution using a syringe, and then placed in an ultrasonic cleaner for 8 minutes at an ultrasonic power of 400 W, and magnetically stirred at 65°C for 2 hours to obtain a modified chrysin nanosuspension.
[0053] S2: Preparation of antimicrobial chain extenders
[0054] S2.1: 25 parts by weight of the modified chrysin nanosuspension and 5 parts by weight of copper acetate are mixed in a container, triethylamine is added to adjust the pH to 7.5, and then stirred at a stirring speed of 200 rpm for 2 hours, and then placed in a vacuum drying oven at a temperature of 40° C. to obtain copper ion coordinated modified chrysin;
[0055] S2.2: The copper ion coordinated modified chrysin obtained in step S2.1 and 10 parts by weight of 1,4-butanediol are placed in a container, 20 parts by weight of anhydrous tetrahydrofuran are added and stirring is continued for 1.5 hours to fully mix the copper ion coordinated modified chrysin and 1,4-butanediol to obtain an antibacterial chain extender.
[0056] S3: Chain extension polymerization of polyurethane prepolymer
[0057] S3.1: 25 parts by weight of polycaprolactone diol were placed in a vacuum oven at 115°C for dehydration for 2 hours, and the temperature was cooled to 75°C while maintaining the vacuum environment, and then taken out, and then placed in a container equipped with a stirring device, 10 parts by weight of isophorone diisocyanate were added, and the temperature was kept at 80°C after heating in an oil bath, and the stirring was maintained for 25 minutes, and 0.03wt% of dibutyltin dilaurate was added dropwise by a syringe, and then nitrogen was introduced for protection, and the polyurethane prepolymer was obtained after keeping the temperature for 3 hours;
[0058] S3.2: Keep the temperature of the polyurethane prepolymer obtained in step S3.1 at 80°C, then quickly add the antibacterial chain extender obtained in step S2.2, mix thoroughly at a stirring speed of 400 rpm, then keep the reaction warm for 3 hours, place it in a vacuum oven at 100°C for 3 hours, then place it in a forced air drying oven and force dry it at 60°C for 10 hours to obtain an antibacterial high-elastic TPU.
[0059] S4: Composite of antibacterial and highly elastic TPU materials
[0060] S4.1: Graphene oxide is prepared by using an improved Hummers method, 20 parts by weight of graphene oxide is taken and added to a container containing 150 parts by weight of ethanol, and then 0.3 parts by weight of silane coupling agent KH570 is added while stirring, and the mixture is reacted at 45°C for 2 hours to obtain a graphene oxide solution, the graphene oxide solution is formed into a film by vacuum filtration and placed in an oven at 55°C for drying to obtain a graphene oxide film, the graphene oxide film is suspended in a high-pressure reactor by a thin wire, and then 20 parts by weight of hydrogen iodide solution is added below, and the graphene oxide film is heated to 100°C for 2 hours of steam reduction, and then rinsed with ethanol and distilled water in turn, and then placed in a vacuum drying oven at 60°C for drying to obtain graphene conductive paper;
[0061] S4.2: Take 80 parts by weight of antibacterial high-elastic TPU, 3 parts by weight of zircon powder, 0.8 parts by weight of epoxy soybean oil, 1 part by weight of stearic acid and 1 part by weight of diisopropylbenzene peroxide, put them in a high-speed mixer for high-speed mixing to obtain a premix, add the premix into a twin-screw extruder, extrude it and then calender it to obtain a TPU composite film with a thickness of 1 mm, coat the upper and lower surfaces of the graphene conductive paper obtained in step S4.1 with epoxy resin adhesive, and then overlap and press it in a sandwich structure of TPU composite film-graphene conductive paper-TPU composite film to obtain a scratch-resistant antibacterial TPU composite material.
[0062] Example 3
[0063] A scratch-resistant antibacterial TPU composite material and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0064] S1: Preparation of modified chrysin nanosuspension
[0065] S1.1: 4 parts by weight of chrysin are placed in a container, and then 20 parts by weight of anhydrous pyridine are added and stirred until the chrysin is completely dissolved to obtain a chrysin solution, and then 1 part by weight of succinic anhydride and 40 parts by weight of anhydrous pyridine are mixed and placed in a container, stirred at a stirring speed of 800 rpm for 2 minutes, and then placed in an oven, and the oven temperature is adjusted to 65°C and heated for 30 minutes. After taking out, the mixture is stirred again at a stirring speed of 800 rpm for 3 minutes, and then continued to be placed in an oven and heated at a temperature of 70°C for 25 minutes to obtain a succinic anhydride solution, and the chrysin solution is added dropwise to the succinic anhydride solution under stirring. After the addition is completed, the mixture is placed in an oven at 65°C and heated for 8 hours, cooled to room temperature, and then allowed to stand overnight at 3°C, and then rotary evaporated at a temperature of 70°C for 30 minutes, and then 60 parts by weight of tetrahydrofuran are added to dissolve the mixture to obtain a mixed organic solvent;
[0066] S1.2: Poloxamer 188, carbomer and deionized water are mixed and stirred at a mass ratio of 1:1:150 to obtain a stabilizer solution, 20 parts by weight of the stabilizer solution are placed in a container, and then 1 part by weight of the mixed organic solvent is quickly injected into the stabilizer solution using a syringe, and then placed in an ultrasonic cleaner for 10 minutes at an ultrasonic power of 450 W, and magnetically stirred at 70°C for 3 hours to obtain a modified chrysin nanosuspension.
[0067] S2: Preparation of antimicrobial chain extenders
[0068] S2.1: 20 parts by weight of the modified chrysin nanosuspension and 4 parts by weight of copper acetate are mixed in a container, triethylamine is added to adjust the pH to 8, and the mixture is stirred at a stirring speed of 250 rpm for 3 hours, and then dried in a vacuum drying oven at a temperature of 50° C. to obtain copper ion coordinated modified chrysin;
[0069] S2.2: The copper ion coordinated modified chrysin obtained in step S2.1 and 8 parts by weight of 1,4-butanediol are placed in a container, 18 parts by weight of anhydrous tetrahydrofuran are added and stirring is continued for 1.5 hours to fully mix the copper ion coordinated modified chrysin and 1,4-butanediol to obtain an antibacterial chain extender.
[0070] S3: Chain extension polymerization of polyurethane prepolymer
[0071] S3.1: 20 parts by weight of polycaprolactone diol were placed in a vacuum oven at 120°C for dehydration for 3 hours, and the mixture was taken out after being cooled to 80°C in a vacuum environment. The mixture was then placed in a container equipped with a stirring device, and 8 parts by weight of isophorone diisocyanate were added. The mixture was heated in an oil bath and the temperature was maintained at 85°C. After stirring for 30 minutes, 0.05 wt% of dibutyltin dilaurate was added dropwise using a syringe, and nitrogen was introduced for protection. The polyurethane prepolymer was obtained after being kept warm for 4 hours.
[0072] S3.2: Keep the temperature of the polyurethane prepolymer obtained in step S3.1 at 85°C, then quickly add the antibacterial chain extender obtained in step S2.2, mix thoroughly at a stirring speed of 450 rpm, then keep the reaction warm for 3.5 hours, place it in a vacuum oven at 105°C for 4 hours, then place it in a forced air drying oven and force dry it at 65°C for 12 hours to obtain an antibacterial high-elastic TPU.
[0073] S4: Composite of antibacterial and highly elastic TPU materials
[0074] S4.1: Graphene oxide is prepared by an improved Hummers method, 15 parts by weight of graphene oxide is taken, added to a container containing 120 parts by weight of ethanol, and then 0.2 parts by weight of silane coupling agent KH570 is added while stirring, and the mixture is reacted at 65°C for 3 hours to obtain a graphene oxide solution, the graphene oxide solution is formed into a film by vacuum filtration and placed in an oven at 60°C for drying to obtain a graphene oxide film, the graphene oxide film is suspended in a high-pressure reactor by a thin wire, and then 15 parts by weight of hydrogen iodide solution is added below, and the graphene oxide film is heated to 105°C for 3 hours of steam reduction, and then rinsed with ethanol and distilled water in turn, and then placed in a vacuum drying oven at 65°C for drying to obtain graphene conductive paper;
[0075] S4.2: Take 60 parts by weight of antibacterial high-elastic TPU, 2 parts by weight of zircon powder, 0.6 parts by weight of epoxy soybean oil, 0.8 parts by weight of stearic acid and 0.8 parts by weight of diisopropylbenzene peroxide, put them in a high-speed mixer for high-speed mixing to obtain a premix, add the premix into a twin-screw extruder, extrude it and then calender it to obtain a TPU composite film with a thickness of 2 mm, coat the upper and lower surfaces of the graphene conductive paper obtained in step S4.1 with epoxy resin adhesive, and then overlap and press it in a sandwich structure of TPU composite film-graphene conductive paper-TPU composite film to obtain a scratch-resistant antibacterial TPU composite material.
[0076] Comparative Example 1
[0077] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 removes step S1 and step S2.1, replaces the copper ion coordinated modified chrysin in step S2.2 with an equal mass of 1,4-butanediol to obtain a 1,4-butanediol chain extender, and replaces the antibacterial chain extender in step S3.2 with a 1,4-butanediol chain extender. The remaining steps are the same as in Example 1, and the obtained antibacterial high-elastic TPU is recorded as Comparative Example 1.
[0078] Comparative Example 2
[0079] Compared with Example 1, the difference of Comparative Example 2 is that, in Comparative Example 2, the modified chrysin nanosuspension in step S2.1 is replaced with an equal mass of 1,4-butanediol to obtain copper ion coordinated 1,4-butanediol, and the copper ion coordinated modified chrysin in step S2.2 is replaced with copper ion coordinated 1,4-butanediol. The remaining steps are the same as in Example 1, and the obtained antibacterial high-elastic TPU is recorded as Comparative Example 2.
[0080] Comparative Example 3
[0081] Compared with Example 1, the difference of Comparative Example 3 is that copper acetate is not added in step S2.1 to obtain modified chrysin, the copper ion coordinated modified chrysin in S2.2 is replaced by modified chrysin, and the remaining steps are the same as those in Example 1. The obtained antibacterial and highly elastic TPU is recorded as Comparative Example 3.
[0082] Comparative Example 4
[0083] Compared with Example 1, the difference of Comparative Example 4 is that Comparative Example 4 removes step S1.1, replaces the mixed organic solvent in step S1.2 with 4 parts by weight of chrysin to prepare a chrysin nanosuspension, and replaces the modified chrysin nanosuspension in step S2.1 with a chrysin nanosuspension. The remaining steps are the same as in Example 1, and the obtained antibacterial high-elastic TPU is recorded as Comparative Example 4.
[0084] Comparative Example 5
[0085] Compared with Example 1, the difference of Comparative Example 5 is that, in Comparative Example 5, poloxamer 188 and carbomer are not added in step S1.2 to obtain a modified chrysin suspension, and the modified chrysin nanosuspension in step S2.1 is replaced by a modified chrysin suspension, and the remaining steps are the same as in Example 1. The obtained antibacterial high-elastic TPU is recorded as Comparative Example 5.
[0086] Experiment 1: The antibacterial high-elastic TPU prepared in Examples 1-3 and Comparative Examples 1-5 were respectively subjected to mechanical property tests using a universal tensile testing machine according to ISO37:2005 standard, with a uniform tensile rate of 100 mm / min. The test results are recorded as shown in Table 1.
[0087] Table 1: Mechanical properties of antibacterial high elastic TPU
[0088] Mechanical properties Tensile stress / MPa Elongation at break / % <![CDATA[Toughness / MJ·m -3 > Self-repair efficiency / % Example 1 4.78 1504 37.4 100 Example 2 4.54 1518 38.5 99.5 Example 3 4.88 1495 36.1 100 Comparative Example 1 6.33 451 12.5 5 Comparative Example 2 5.84 604 23.7 28 Comparative Example 3 5.17 813 17.4 58 Comparative Example 4 4.87 1386 34.3 91 Comparative Example 5 5.01 1401 35.1 93
[0089] Tensile stress refers to the force that produces uniform plastic deformation of TPU material under the action of tensile force. The lower the tensile stress, the better the softness and ductility of TPU material. The elongation at break refers to the maximum deformation that TPU material can withstand during the stretching process. The higher the elongation at break, the better the ductility of TPU material. It can withstand large deformation without breaking, which means that the material has better tensile resistance, flexibility and tear resistance. Toughness refers to the ability of the material to absorb energy under the action of external force. The level of toughness reflects the impact resistance and fatigue resistance of TPU material. Self-healing ability refers to the ability of TPU material to restore its original shape and performance under certain conditions after being damaged. It is usually evaluated by whether the material can heal itself after cracks, scratches or cuts. Self-healing ability directly affects the durability and reliability of TPU material during long-term use. For TPU material, tensile stress, elongation at break, toughness and self-healing ability can reflect the mechanical properties of TPU material.
[0090] It can be seen from Table 1 that the mechanical properties of the antibacterial high-elastic TPU prepared in Examples 1-3 are better than those of Comparative Examples 1-5. It can be seen from Example 1 and Comparative Example 1 that the preparation of an antibacterial chain extender and its application in the chain extension polymerization of a polyurethane prepolymer can greatly enhance the mechanical properties of the TPU material. It can be seen from Example 1, Comparative Example 2 and Comparative Example 3 that the removal of modified chrysin and the removal of copper acetate will both lead to a decrease in the mechanical properties of the TPU material. This proves that the hydroxyl group in the modified chrysin and the carboxyl group coordinated with copper ions have a synergistic effect and can jointly construct a dynamic cross-linked network to improve the mechanical properties and self-repairing ability of the TPU material.
[0091] It can be seen from Example 1 and Comparative Examples 4-5 that the mechanical properties of the antibacterial and highly elastic TPU can be improved by modifying chrysin with succinic anhydride. It can also be seen that preparing a stabilizer solution and uniformly dispersing the modified chrysin in an aqueous solution with a smaller particle size can improve the coordination effect of copper ions and modified chrysin, thereby improving the mechanical properties of the TPU material.
[0092] Experiment 2: Take 0.1g of the antibacterial high-elastic TPU prepared in Examples 1-3 and Comparative Example 3, respectively, and add them to containers filled with 80mL of sterile water, and ultrasonically disperse for 25 minutes. Add 1mL of 10 7 CFU / mL of bacterial suspension was recorded as the experimental group. Take another container filled with 80mL of sterile water and add 1mL of 10 7 The bacterial suspension of 100 CFU / mL was the blank control group. The above containers were placed in an oscillating incubator and cultured at 37°C and 250rpm for 30 minutes. 1 mL of solution was taken from each container and spread on a culture dish. The culture was cultured at 37°C for 48 hours and the colonies were counted. Three parallel experiments were performed, and the average colony count of the experimental group was recorded as A, and the average colony count of the blank control group was recorded as B. The inhibition rate = (BA) / B×100%. Staphylococcus aureus and Escherichia coli were selected as bacterial species. The data were recorded and tabulated as shown in Table 2.
[0093] Table 2: Antibacterial rate of antibacterial high-elastic TPU
[0094]
[0095]
[0096] It can be seen from the data of Example 1 and Comparative Example 3 that the antibacterial rate of Comparative Example 3 in which copper ions are not introduced into the TPU material is much lower than that of Example 1, which can prove that modified chrysin coordinated with copper ions and introduced into the TPU material can provide the TPU material with excellent antibacterial ability.
[0097] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a scratch-resistant antibacterial TPU composite material, characterized in that: The following steps are involved: S1: Preparation of modified chrysin nanosuspension The chrysin solution is prepared by dissolving chrysin in anhydrous pyridine, succinic anhydride is dissolved in anhydrous pyridine by heating and stirring to obtain a succinic anhydride solution, the chrysin solution is added dropwise to the succinic anhydride solution under stirring, and then heated, kept at low temperature overnight, and rotary evaporated, and then dissolved by tetrahydrofuran to obtain a mixed organic solvent, and a stabilizer solution is prepared by uniformly mixing poloxamer 188, carbomer and deionized water, and the mixed organic solvent is quickly injected into the stabilizer solution and ultrasonically treated, and magnetically stirred to obtain a modified chrysin nanosuspension; S2: Preparation of antimicrobial chain extenders The modified chrysin nanosuspension and copper acetate are mixed and the pH is adjusted, and the copper ion coordinated modified chrysin is obtained after stirring and drying, and the copper ion coordinated modified chrysin and 1,4-butanediol are placed in anhydrous tetrahydrofuran and stirred to obtain an antibacterial chain extender; S3: Chain extension polymerization of polyurethane prepolymer The polycaprolactone diol is dehydrated and dried, and then mixed with isophorone diisocyanate to obtain a polyurethane prepolymer, and then an antibacterial chain extender is quickly added to the polyurethane prepolymer while maintaining a high temperature, and the reaction is fully stirred and dried to obtain an antibacterial high-elastic TPU; S4: Composite of antibacterial and highly elastic TPU materials Graphene oxide was prepared by an improved Hummers method. Graphene oxide, ethanol and silane coupling agent KH570 were mixed and reacted to obtain a graphene oxide solution. The graphene oxide solution was then vacuum filtered to form a membrane to obtain a graphene oxide film, which was then reduced by hydrogen iodide vapor to obtain a graphene conductive paper. Antibacterial high-elastic TPU, zircon powder, epoxy soybean oil, stearic acid and diisopropylbenzene peroxide were mixed at a high speed and then extruded and calendered to obtain a TPU composite film. Epoxy resin adhesive was applied to the surface of the graphene conductive paper and then the TPU composite film-graphene conductive paper-TPU composite film sandwich structure was stacked and pressed to obtain a scratch-resistant antibacterial TPU composite material.
2. The method for preparing a scratch-resistant antibacterial TPU composite material according to claim 1, characterized in that: Step S1: Preparation of modified chrysin nanosuspension, comprising the following steps: S1.1: 4-6 parts by weight of chrysin is placed in a container, and then 20-25 parts by weight of anhydrous pyridine is added and stirred until the chrysin is completely dissolved to obtain a chrysin solution. Then 1-2 parts by weight of succinic anhydride and 40-50 parts by weight of anhydrous pyridine are mixed and placed in a container, stirred at a stirring speed of 600-800 rpm for 1-2 minutes, and then placed in an oven, and the oven temperature is adjusted to 60-65°C and heated for 25-30 minutes. After taking out, the mixture is stirred again at a stirring speed of 600-800 rpm. The mixture was stirred at 400 ° C for 2-3 minutes, and then continued to be placed in an oven and heated at a temperature of 65-70 ° C for 20-25 minutes to obtain a succinic anhydride solution, and the chrysin solution was added dropwise to the succinic anhydride solution under stirring. After the addition was completed, it was placed in an oven at 60-65 ° C and heated for 6-8 hours. After cooling to room temperature, it was allowed to stand at 2-3 ° C overnight, and then rotary evaporated at a temperature of 65-70 ° C for 25-30 minutes, and then 60-80 parts by weight of tetrahydrofuran was added to dissolve it to obtain a mixed organic solvent; S1.2: Poloxamer 188, carbomer and deionized water are mixed and stirred at a mass ratio of 1: (1-1.5): (150-180) to obtain a stabilizer solution, 20-25 parts by weight of the stabilizer solution are placed in a container, and then 1-2 parts by weight of a mixed organic solvent are quickly injected into the stabilizer solution using a syringe, and then placed in an ultrasonic cleaning machine for 8-10 minutes at an ultrasonic power of 400-450 W, and magnetically stirred at 65-70° C. for 2-3 hours to obtain a modified chrysin nanosuspension.
3. The method for preparing a scratch-resistant antibacterial TPU composite material according to claim 2, characterized in that: Step S2: Preparation of an antimicrobial chain extender, comprising the following steps: S2.1: 20-25 parts by weight of the modified chrysin nanosuspension and 4-5 parts by weight of copper acetate are mixed in a container, a pH adjuster is added to adjust the pH to 7.5-8, and then stirred at a stirring speed of 200-250 rpm for 2-3 hours, and then placed in a vacuum drying oven at a temperature of 40-50° C. to obtain copper ion coordinated modified chrysin; S2.2: The copper ion coordinated modified chrysin obtained in step S2.1 and 8-10 parts by weight of 1,4-butanediol are placed in a container, 18-20 parts by weight of anhydrous tetrahydrofuran are added and stirred for 1.5-2 hours to fully mix the copper ion coordinated modified chrysin and 1,4-butanediol to obtain an antibacterial chain extender.
4. The method for preparing a scratch-resistant antibacterial TPU composite material according to claim 3, characterized in that: Step S3, chain extension polymerization of the polyurethane prepolymer, comprises the following steps: S3.1: 20-25 parts by weight of polycaprolactone diol is placed in a vacuum oven at 115-120°C for dehydration for 2-3 hours, and the temperature is cooled to 75-80°C while maintaining the vacuum environment. Then, the mixture is taken out and placed in a container equipped with a stirring device, and 8-10 parts by weight of isophorone diisocyanate is added. The mixture is heated in an oil bath and maintained at 80-85°C. After stirring for 25-30 minutes, stirring is continued, and 0.03-0.05wt% of dibutyltin dilaurate is added dropwise using a syringe, and then nitrogen is introduced for protection. After heat preservation for 3-4 hours, a polyurethane prepolymer is obtained; S3.2: Keep the temperature of the polyurethane prepolymer obtained in step S3.1 at 80-85°C, then quickly add the antibacterial chain extender obtained in step S2.2, mix thoroughly at a stirring speed of 400-450rpm, then keep warm for reaction for 3-3.5 hours, place in a vacuum oven at 100-105°C for 3-4 hours, then place in a forced air drying oven, and force dry at 60-65°C for 10-12 hours to obtain an antibacterial high-elastic TPU.
5. The method for preparing a scratch-resistant antibacterial TPU composite material according to claim 4, characterized in that: Step S4, compounding of antibacterial high-elastic TPU material, comprises the following steps: S4.1: Graphene oxide is prepared by an improved Hummers method, 15-20 parts by weight of graphene oxide is taken, added to a container containing 120-150 parts by weight of ethanol, and then 0.2-0.3 parts by weight of silane coupling agent KH570 is added while stirring, and the mixture is reacted at 45-65°C for 2-3 hours to obtain a graphene oxide solution, the graphene oxide solution is formed into a film by vacuum filtration and placed in an oven at 55-60°C for drying to obtain a graphene oxide film, the graphene oxide film is suspended in a high-pressure reactor by a thin wire, and then 15-20 parts by weight of hydrogen iodide solution is added below, and the graphene oxide film is heated to 100-105°C for 2-3 hours of steam reduction, and then rinsed with ethanol and distilled water in turn, and then placed in a vacuum drying oven at 60-65°C for drying to obtain graphene conductive paper; S4.2: Take 60-80 parts by weight of antibacterial high-elastic TPU, 2-3 parts by weight of zircon powder, 0.6-0.8 parts by weight of epoxy soybean oil, 0.8-1 parts by weight of stearic acid and 0.8-1 parts by weight of diisopropylbenzene peroxide, put them in a high-speed mixer for high-speed mixing to obtain a premix, add the premix into a twin-screw extruder for extrusion and then calendering to obtain a TPU composite film, coat the upper and lower surfaces of the graphene conductive paper obtained in step S4.1 with epoxy resin adhesive, and then overlap and press in a sandwich structure of TPU composite film-graphene conductive paper-TPU composite film to obtain a scratch-resistant antibacterial TPU composite material.
6. The method for preparing a scratch-resistant antibacterial TPU composite material according to claim 3, characterized in that: The pH adjuster in step S2.1 is triethylamine.
7. The method for preparing a scratch-resistant antibacterial TPU composite material according to claim 5, characterized in that: The thickness of the TPU film formed by calendering the premix in step S4.2 after being extruded through a twin-screw extruder is 1-2 mm.
8. A scratch-resistant antibacterial TPU composite material, characterized in that: The antibacterial TPU composite material is prepared by the method for preparing the scratch-resistant antibacterial TPU composite material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Nano-modified waterborne polyurethane composite material and preparation method thereof
CN116135926A
Flame-retardant and antibacterial waterborne polyurethane and preparation method thereof
CN116199853A
Self-healing antibacterial polyurethane elastomer and preparation method thereof
CN117343273A
Polyurethane antibacterial composite material and preparation method thereof
CN117511181A
Antifungal polyurethane resin composition and manufacturing method
JP2001213930A